Exportações e atividade econômica das regiões brasileiras - Azevedo, Fernanda Bechuate de Souza (2018)
This dissertation investigates the relationship between exports and the Brazilian regions economic activity during the years 2000. For this, the work is based on the arguments of Kaldor (1966) and Thirlwall (2005), who emphasize that the economies growth is given by the demand factors side, mainly industrialized goods exports. In addition, it is assumed that the type of exported product is relevant to explain growth, as pointed out by Sachs and Warner (1995) and Rodrik (2006). The analysis of the regions international trade profile in the years 2000 to 2016 shows that they have different degrees of specialization. The more developed regions, such as the South and Southeast, have a larger share of manufactured goods exports, and the less developed regions carry more weight in basic products. However, there is a trend of increasing commodities share in regional exports baskets. For the empirical analysis, the Autoregressive Distributed Lags Models (ARDL) methodology was used to estimate the total exports and by the type of products (basic, semi-manufactured and manufactured) on the Gross Domestic Product (GDP) of each Brazilian region in the period from 2003 and 2016, also considering some control variables linked to the regions internal context, such as consumption and investment. The results indicate that, in the long run, regional exports were not relevant to explain the economic activity performance, contrary to what was expected in the literature. For the short run, exports generally contributed to the results of regional GDPs. Overall, both in the short and long run, domestic variables, especially consumption and investment, were more important in explaining regional economic activity.